DEVELOPMENTAL STAGES OF LIABILITY FOR CRIMES AGAINST PEACE AND SECURITY OF MANKIND - Azamatov Shohijahon Alisher O'g'li (Journals Park Publishing, 2023)
It is apparent that any kind of legal norms have undergone a number of stages of development to date in order to become the current condition. Such kind of phenomenon can be observed in the case of the liability for crimes against peace and security of mankind. As is known to all, these crimes are considered as international ones. Despite the fact that these crimes do not have long history, they hold great significance in the international law. This article is dedicated to highlighting the stages of development so far.
Keywords: conventions, tribunals, international courts, aggression, peace, security of mankind, genocide, ecocide, mass destruction weapons, penal code, war crimes, humanitarian laws, war customs, law enforcement agencies.